Recent advances in multifunctional proppant technology and increased well output with micro and nano proppants - Danso, D.K. (Elsevier B.V., 2021)
Proppants have evolved from their primary role of preventing fracture closure to performing technically functional roles within reservoirs. This paper presents an extensive review of recent advances in functional proppant technology. Multifunctional proppant roles, such as the enhancement of multiphase flow of reservoir fluids, delivery of CO2 for enhanced gas recovery, detection of fracture geometry, removal of contaminants, fracture moderation, treatment of flowback water, as well as proppant flow back retardation are presented. Advances in proppants with good transport and placement properties, such as, self suspended proppants and in-situ generated proppants were further addressed. Recent field and laboratory works suggested that conventionally sized proppants (<149 Î¼m) leave the majority of stimulated reservoir unpropped. The role of micro and nano proppants in recovering these untapped areas are critically reviewed. The optimum size of micro and nanoproppant for effective propping of induced unpropped fractures were discussed. Due to the increasing proppants pumped per lateral foot, cheap sources of regional industrial waste materials such as granitic waste powder, used foundry sand, and blast furnace slag are recommended as potential sources of micro and nano proppants. These cost-effective materials could complement the conventional sand proppants, and their application for averting the closure of micro-fissures could help in sustaining the environment from excessive regional sand mining. Â© 2020 Elsevier B.V.